Settlement Negotiations with Reference-Dependent Preferences. (1st February 2022) - Rössler, Christoph; Friehe, Tim
Abstract: This article analyzes pretrial bargaining between litigants with reference-dependent preferences. We build on Bebchuk (1984, "Litigation and Settlement under Imperfect Information, " 15 Rand Journal of Economics 404–15) and, motivated by empirical evidence, assume that the referent is based on expectations. We find that reference dependence on behalf of plaintiffs increases the settlement probability. The fact that preferences are reference-dependent meaningfully influences comparative statics predictions. In our extensions, we discuss the role of fee shifting, the effect of having the referent based on the status quo instead of on expectations, and risk aversion.